PENGARUH MODEL PEMBELAJARAN ROLE PLAYIING TERHADAP KETERAMPILAN BERBICARA PADA PEMBELAJARAN BAHASA INDONESIA KELAS III SD NEGERI 101740 TANJUNG SELAMAT - Elisabet Malau, Novia; Imelda; Heka Maya Sari Br Sembiring; Darinda Sofia Tanjung; Dyan Wulan Sari HS; Patri Janson Silaban (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
This study aims to determine the effect of the Role Playing learning model on students’ speaking skills in Indonesian language learning for third-grade students at SD Negeri 101740 Tanjung Selamat. The background of this research is based on the low speaking skills of students, including a lack of confidence, anxiety when speaking in front of the class, and the limited use of varied teaching methods. The Role Playing model was chosen because it is considered capable of encouraging students to actively engage and express themselves through relevant and enjoyable role simulations. This research uses a quantitative approach with a quasi-experimental method. Data were collected through questionnaires and speaking skill tests. The sample consisted of 32 students from the third grade of SD Negeri 101740 Tanjung Selamat. Data were analyzed using normality tests, correlation tests, and hypothesis testing. The results showed that there is a positive and significant effect of using the Role Playing learning model on students’ speaking skills. The implementation of this model increases students' self-confidence, fluency in speaking, and their ability to construct proper sentences within the context of Indonesian language learning.